Statin regulated ERK5 stimulates tight junction formation and reduces permeability in human cardiac endothelial cells. Issue 1 (3rd August 2017) - Wilkinson, Emma L.; Sidaway, James E.; Cross, Michael J.
Abstract : The MEKK3/MEK5/ERK5 signaling axis is required for cardiovascular development in vivo. We analyzed the physiological role of ERK5 in cardiac endothelial cells and the consequence of activation of this kinase by the statin class of HMG Co‐A reductase inhibitor drugs. We utilized human cardiac microvascular endothelial cells (HCMECs) and altered ERK5 expression using siRNA mediated gene silencing or overexpression of constitutively active MEK5 and ERK5 to reveal a role for ERK5 in regulating endothelial tight junction formation and cell permeability. Statin treatment of HCMECs stimulated activation of ERK5 and translocation to the plasma membrane resulting in co‐localization with the tight junction protein ZO‐1 and a concomitant reduction in endothelial cell permeability. Statin mediated activation of ERK5 was a consequence of reduced isoprenoid synthesis following HMG Co‐A reductase inhibition. Statin pretreatment could overcome the effect of doxorubicin in reducing endothelial tight junction formation and prevent increased permeability. Our data provide the first evidence for the role of ERK5 in regulating endothelial tight junction formation and endothelial cell permeability. Statin mediated ERK5 activation and the resulting decrease in cardiac endothelial cell permeability may contribute to the cardioprotective effects of statins in reducing doxorubicin‐induced cardiotoxicity. Abstract : Extracellular signal regulated kinase 5 (ERK5) is required for cardiovascular development in vivo. We have utilized human cardiac endothelial cells to show that ERK5 regulates tight junction formation and permeability in these cells. Statins stimulate ERK5 activity resulting in decreased permeability, which can potentially protect against the adverse effects of cardiotoxic drugs.